Follow‐up evaluation of patients with liver test abnormalities detected during SARS‐CoV2 infection. Issue 9 (26th June 2022) - Canillas, Lidia; Broquetas, Teresa; Carrión, José A.; Pagano, Giulia; Soriano, Agnès; Garrido, Esther; Fernández, Rosa; Viu, Ana; Romero, Judit; Díaz, Gemma; Cañete, Nuria; Coll, Susana; et al.
Abstract: Abnormal liver function tests (A‐LFTs) during admission for coronavirus disease‐19 (COVID‐19) are frequent, but its evolution after COVID‐19 resolution remains unexplored. We evaluated factors related to A‐LFTs during COVID‐19 and assessed the liver outcome after patients' discharge. This is a observational study including: (1) retrospective analysis of variables related to A‐LFTs during COVID‐19; and (2) follow‐up evaluation with blood test, transient elastography and liver biopsy in those with persistent A‐LFTs. A‐LFTs were defined according to CTCAEv4.0. Among 595 patients, 366 (61.5%) showed A‐LFTs. The ratio of partial pressure of oxygen and inspired oxygen fraction (P/F) below 200, ferritin ≥1000 ng/mL, male gender and antibiotic and immunomodulatory treatments were related to A‐LFTs. Follow‐up evaluation was performed in 153 individuals. Persistent A‐LFTs at follow‐up was similar in patients with/without A‐LFTs during admission (14.1% vs. 4.9%, p = 0.104). Fifteen (93%) and 58 (39%) patients with/without A‐LFTs at follow‐up showed metabolic fatty liver disease criteria ( p < 0.001), which were histologically confirmed. In conclusion, A‐LFTs during COVID‐19 were related to infection severity. Abnormalities remitted at follow‐up in >80% of patients, and no correlation between A‐LFTs at admission and at follow‐up was found. Most patients with A‐LFTs at follow‐up had non‐invasive and histologically proven fatty liver disease.